Analysis Of Procedures References Implementatiom National Health at Ujoh Bilang Public Health Center Mahakam Ulu District - Azizatul Hamidiyah; Rindha Mareta Kusumawati (Universitas Widya Gama Mahakam Samarinda, 2021)
Background: The number of referrals at Ujoh Bilang Health Center in 2016 wa 31 referrals in 2017 there were 37 referrals in 2018 there were 41 referrals and untiil april 2019 there were 114 referrals. Objectives: The research objective was to analyze procedures for implementing the referral system at Ujoh Bilang Public Health Center. Research Metodes: This Type of research is qualitative with a case study approach through interviews, observation and documentation of 4 informants namely doctors, nurses, the Head of Administration and the Head of Community Health Center. Data analysis techniques are data collection, reduction, data presentation and conclusion drawing Findings: The results of the study was to procedures for implementing the referral system based on National Referral System Guidelines but the public health center can’t reach refferal health facilities beacuse online network facilities were not available. The referral procedure at Ujoh Bilang Helath Center is in accordance with the National Referral System Guidlines but the puskesmas does not contact the referral destination health facility before the patient is referred because there is ni inline referral Conclusion: It was concluded that the provision of an internet network was inadequate, the puskesmas did not contact health facilities before seeing patients. Suggestionsfor the Ujoh Bilang Public Health Center Are to Provide an internet network in the form of wifi